Hubungan Kepatuhan Minum Obat Tablet Zat Besi (Fe) Pada Ibu Hamil Dengan Risiko Kejadian Anemia Di Puskesmas Bantargebang - Pratama Febrianty, Diva; Meliyana, Ernauli; Indrawati, Lina (PT. Pubsains Nur Cendekia, 2023)
Background: During pregnancy, women really need good nutritional intake, starting from food and iron (Fe) supplements. Pregnant women are at risk of experiencing anemia, especially due to iron (Fe) deficiency. Objective: To determine the relationship between adherence to taking iron (Fe) tablet medication in pregnant women and the risk of anemia at the Bantargebang Community Health Center. Method: Using a quantitative type of research, which is observational analytical in nature using a cross sectional study design and using Total Sampling sampling techniques, with a sample size of 100 people at the Bantar Gebang Community Health Center. The instrument for measuring the level of compliance of pregnant women uses a questionnaire whose validity and reliability have been tested. Meanwhile, to determine the level of anemia in pregnant women using a hemoglobinometer. Data analysis uses the chi-square formula. Results: Univariate analysis showed that the majority of pregnant women adhered to taking iron (Fe) tablets, 58 respondents (58.0%). Most pregnant women did not experience anemia, 54 respondents (54.0%). Bivariate analysis showed that the majority of pregnant women who were compliant in taking tablet medication (Fe) did not experience anemia as many as 42 respondents (42.0%) and the statistical test results using chi squere were obtained at 0.00 < 0.05. Conclusion: There is a relationship between adherence to taking iron (Fe) tablets in pregnant women and the risk of anemia at the Bantargebang Community Health Center.